Comparison of three surgical approaches for staging lymphadenectomy in high‐risk endometrial cancer. Issue 3 (12th January 2017) - Pulman, Katherine J.; Dason, Ebernella S.; Philp, Lauren; Bernardini, Marcus Q.; Ferguson, Sarah E.; Laframboise, Stéphane; Atenafu, Eshetu G.; May, Taymaa
Abstract: Objective: To compare laparotomy, laparoscopy, and robotic surgical approaches to lymphadenectomy for high‐risk endometrial cancer staging. Methods: A retrospective cohort study enrolled patients who underwent surgery for pathologic high‐risk endometrial carcinoma at the University Health Network, Toronto, Canada, between January 1, 2005 and December 31, 2013. The primary outcome, the median number of nodes retrieved, was compared based on surgical technique. The secondary outcome was the detection of metastatic nodes. Results: A total of 176 patients who underwent surgery for high‐risk endometrial cancer were included, of whom 147 (83.5%) had pelvic and 78 (44.3%) had para‐aortic lymphadenectomy. Laparotomy, laparoscopy, and robotic approaches were applied for 69 (39.2%), 44 (25.0%), and 63 (35.8%) patients, respectively. Minimally‐invasive staging was associated with an increased proportion of patients undergoing pelvic lymphadenectomy compared with laparotomy ( P= 0.005). The median number of nodes removed in the pelvis and para‐aortic regions did not differ between surgical approaches. The detection of metastatic nodes was also similar between the groups. Increased blood loss ( P< 0.001) and longer hospital admission ( P< 0.001) were observed with laparotomy procedures. Conclusion: All three techniques demonstrated adequate staging of high‐risk endometrial carcinoma. Based on improved peri‐operative outcomes, the use of minimally‐invasive techniques is advocated where appropriate. Abstract : High‐risk endometrial cancer was adequately staged using laparotomy, laparoscopy, and robotic surgery. The results suggest that a minimally invasive approach should be applied when feasible.